Influence of Buddhism and Vedism in Nepalese Co-operatives - Acharya, Sushma (Research Nepal Journal of Development Studies, 2019)
The universal definition of co-operatives is an autonomous association of persons united voluntarily to meet their common economic, social, and cultural needs and aspirations through a jointly-owned and democratically-controlled enterprise. Co-operatives are the community based member oriented and controlled organizations. It based on values of self-help, self-responsibility, equality, equity, democracy and solidarity. Empowerment, reinvesting and upliftment in economic status of people are the main purpose of co-operatives. The main objective of the study is to investigate how co-operatives can act as agents towards sustainable community development and economic development of Nepal through Vedic and Buddhism perspective. Methodologically, it is a comprehensive interpretive analysis through literature review. In conclusion Nepalese co-operatives do not have impacts or influences of godly philosophies neither Vedism nor Buddhism.